Inovasi Pendidikan Dalam Meningkatkan Strategi Mutu Pendidikan - Siti Rahmawati; Kun Nurachadija (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
Educational innovation can be interpreted as the introduction, development, and application of new ideas, concepts, methods, technologies, or approaches in the context of education. Educational innovation aims to transform and improve the way education learns, teaches, and management that have existed before. This study aims to explore and analyze the role of educational innovation in improving education quality strategies at various levels of education. The focus of this research is to understand how educational innovation can make a positive contribution to improving education quality strategies, including more effective teaching and better learning outcomes. The research methods used include literature reviews, case studies, and analysis of data collected from various sources related to the implementation of educational innovations. Data was collected through stakeholder interviews, direct observation, and document analysis. The results show that educational innovation has great potential to improve education quality strategies. Through the use of digital technologies, such as learning software, online platforms, or mobile devices, teaching can become more interactive, participatory, and adaptive. Teachers can use the various tools and resources available to create more engaging and relevant learning experiences for students.